دور أخلقة العمل السّياسي على التنمية الوطنية في الجزائر. دراسة تحليلية نقدية - بلعسل محمد; زايدي عبد العزيز (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تسعى هذه الدراسة لتحليل و مناقشة موضوع أخلقة العمل السياسي و دورها في تحقيق التنمية الوطنية في الجزائر. فحالة الفساد السياسي التي عرفتها الدولة في الفترات السابقة في جميع القطاعات حتّمت على السّلوك السّياسي الرسمي الحالي تبني فكرة أخلقة العمل السياسي بغية تحقيق التنمية الوطنية و ترقية المجتمع نحو الأفضل. يتم تناول موضوع الدراسة بطريقة تحليلية نقدية، و من بين النتائج التي توصلت اليها الدراسة أن أخلقة العمل السياسي هو حجر أساس لبناء حاضر الجزائر و مستقبلها، و يعد حتمية لتحقيق التنمية و تطوير الاقتصاد الوطني و ترقية المجتمع نحو التقدم المأمول، خاصة لفئة الشباب الجزائري. This study seeks to analyze and discuss the issue of ethics in political action and its role in achieving national development in Algeria. The state of political corruption that the state has known in previous periods in all sectors made it necessary for the current official political behavior to adopt the idea of ethical political action in order to achieve national development and promote society for the better. The topic of the study is dealt with in an analytical and critical way, and among the findings of the study is that the ethics of political action is a cornerstone of building Algeria’s present and future, and is imperative for achieving development, developing the national economy and promoting society towards the desired progress, especially for the Algerian youth. Keywords: the ethics of political action, national development, Algeria